Management of Choledochal Cyst: Experience from A Tertiary Care Center of Nepal - Shrestha, Sujan; Ghimire, Bikal; Kansakar, Prasan; Bhandari, Ramesh S; Joshi Lakhey, Paleshwan (Journal of Institute of Medicine Nepal, 2021)
Introduction: Choledochal cysts are infrequent congenital cystic dilation of the biliary tract. The aim of this study is to analyze the clinicopathological profile and short-term operative outcomes of patients with choledochal cysts. Methods: This is a retrospective study of 32 consecutive patients of choledochal cyst who underwent multidisciplinary management in last two and half years at Tribhuvan University Teaching Hospital, Kathmandu, Nepal. Results: A total of 32 patients, 9 males and 23 females were operated. The average age at diagnosis was 24.67±16.4 years (range from 2 to 56 years). The most common presenting symptoms were pain 31(96.88%), jaundice 10(31.25%) and mass 5(15.63%). Triad of pain, jaundice and mass was present in 4(12.5%). Transabdominal Ultrasonography (100%) was the initial diagnostic modality followed by Magnetic resonance cholangiopancreatography (MRCP) (68.75%), and contrast enhanced computed tomography (CECT) (31.25%). Endoscopic retrograde cholangiopancreatography (ERCP) was done for stent placement in 3 (9.38%) patients with severe cholangitis. Type IVA (37.5%) was the most common type of CC followed by type IC (31.23%), type IB (15.65%), type IA (12.5%) and type IVB (3.12%). Abnormal pancreaticobiliary duct junction was observed in 3 (9.38%) patients. All patients underwent open cyst excision with Roux-en-Y hepaticojejunostomy (HJ). The overall morbidity was seen in 6 patients (18.75%). There was no mortality. None of our patient had cholangiocarcinoma on pathological examination. Conclusion: Choledochal cyst was common in young females. Type IC and IVA choledochal cyst were the most common types and majority of them were symptomatic. Cyst excision with Roux-en-Y hepaticojejunostomy was the commonest surgical treatment modality and had excellent perioperative outcome.